Historical biogeography and multi-trait evolution in miniature toadlets of the genus Brachycephalus (Anura: Brachycephalidae) - Condez, Thais H.; Haddad, Celio F. B. [UNESP]; Zamudio, Kelly R. (Oxford Univ Press, 2020)
Evolutionary changes towards a miniaturized body plan may directly affect other important phenotypic traits related to the physiology, behaviour and ecology of organisms. The frog genus Brachycephalus is an outstanding example of a radiation of miniaturized species endemic to the Brazilian Atlantic Forest. We inferred ancestral states and historical changes in body size, body colour and hyperossification to test hypotheses about diversification and selective environmental mechanisms leading to the evolution of these specialized traits. The ancestral distribution was associated with high-elevation regions in the northern Serra do Mar mountain range, and diversification in the genus was coincident with important geological and climatic events during the history of the Atlantic Forest. The dynamic historical changes provided an opportunity for multiple lowland lineages and for speciation via dispersal and vicariance in multiple invasions of the highlands. The ancestral Brachycephalus was reconstructed as miniaturized and dull coloured, without hyperossification in the skin, skull or postcranial skeleton. A parallel evolution of phenotypic traits has occurred in northern and southern Atlantic Forest lineages, beginning in the Miocene. Shifts in body size are not related to elevation range or latitude. However, we found a significant correlation between the evolution of hyperossification and aposematism with increasing body size.
Keywords: aposematism; elevation; hyperossification; latitude; miniaturization